PERAN INSTITUSI KEUANGAN SYARIAH SEBAGAI PENGGERAK EKONOMI DAERAH - Ratna (Program Studi Perbankan Syariah, 2022)
Islamic financial institutions play a very important role in supporting Islamic economic growth in Indonesia, especially as a driver of the regional economy. The purpose of this study was to determine the role of Islamic financial institutions as a driver of the regional economy. The objective of this study is to provide a complete design and description of the role of Islamic financial institutions as a driver of the regional economy. Meanwhile, the objectives of the study of Islamic financial institutions as drivers of the regional economy are: (a) Obtaining data on Islamic financial institutions and their specifications; (b) Obtaining data on the potential and identification of problems faced by Islamic financial institutions, in particular the role related to the efforts of Islamic financial institutions to increase access to micro-scale funding for business actors in the regions, the efforts of Islamic financial institutions to help increase regional economic empowerment and productivity of MSMEs, and efforts Islamic financial institutions help increase income and welfare, especially those with low incomes; (c) Analyzing the potential and role of Islamic financial institutions in regional economic development.